일부 초등학생의 학년에 따른 구강보건교육 효과 비교 - 박일순; Il Soon Park; 최은미; Eun Mi Choi; 김혜진; Hye Jin Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives : The purpose of this study is to investigate the effect of oral health educationconducted by a dental hygienist in order to provide some information on intensive oral healtheducation to elementary school students. Methods : Subjects were the students of J and M elementary schools in Seoul from October28 to November 16, 2011. Oral health education was provided by a dental hygienist, and thenthey took the PHP test again to verify the effect of the oral health education. Results : Concerning changes in PHP scores after the oral health education, the scores ofthe students dropped from 2.34 in the pretest to 1.85 in the posttest(p<.001). As to changesin PHP scores by grade after the oral health education, the third graders and sixth graders got2.40 and 1.36, respectively. Regarding satisfaction level with the oral health education, they got4.07 out of five points. Among the items of satisfaction with the oral health education by grade,there were significant gaps in a change of toothbrushing method(p<.001) and a change of dietarycontrol(p<.001) by grade. Conclusions : The finding of the study showed that both the third and sixth graders hadless score in the PHP test and credibility to the effectiveness of the oral health education bythe dental hygienist.